Źródło wszystkich źródeł. O czterech warszawskich tomach Archiwum Ringelbluma - Barbara Engelking (Zagłada Żydów)
The text presents four volumes of the series containing materials from the Ringelblum Archive that concern Warsaw Jews: vol. 5: Getto warszawskie. Życie codzienne [The Warsaw Ghetoo. Everyday Life], ed. Katarzyna Person (2011); vol. 7: Spuścizny [The Legacies], ed. Katarzyna Person (2012); vol. 11: Ludzie i prace „Oneg Szabat” [People and Works of the “Oneg Shabbat”], ed. Aleksandra Bańkowska and Tadeusz Epsztein (2013); vol. 12: Rada Żydowska w Warszawie (1939–1943) [The Jewish Council in Warsaw, 1939–1943], ed. Marta Janczewska (2014).